Comparison of the Representation of Homeopathy from Different Students Audiences - Kessouar, Dalila; Di Scala, Emmanuella (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
Homeopathy is the subject of public controversy that will be characterized as a socio- scientific controversy. Indeed, it has been and still is very controversial within the academic and scientific sphere. Through its history, homeopathy has always oscillated between challenge and integration (Faure, 2002). This study of a student audience is part of the HOMEOCSS societal research project (www.projet-homeoccs.com) which is interested in this controversy and the social representations of homeopathy by various social actors. This work is based on a comparison of the representations of homeopathy of different student audiences at the University of Dijon, France, and will provide an initial approach to this object of study. The challenge will be to better understand the representations of different student audiences in order to identify whether the training program can have an influence on their representations. It asks whether the sociological anchoring of an individual can preferentially influence his representations and whether an individual can, during his life course, change a sociological anchoring. The target audience is composed of students aged between 18 and 25 years old from different university departments: students of Medicine, Psychology and Life and Earth Sciences.